Guardian of Genetic Messenger-RNA-Binding Proteins - Anji, Antje; Kumari, Meena (My University, 2016)
RNA in cells is always associated with RNA-binding proteins that regulate all aspects of RNA metabolism including RNA splicing, export from the nucleus, RNA localization, mRNA turn-over as well as translation. Given their diverse functions, cells express a variety of RNA-binding proteins, which play important roles in the pathologies of a number of diseases. In this review we focus on the effect of alcohol on different RNA-binding proteins and their possible contribution to alcohol-related disorders, and discuss the role of these proteins in the development of neurological diseases and cancer. We further discuss the conventional methods and newer techniques that are employed to identify RNA-binding proteins.
Citation: Anji, A., & Kumari, M. (2016). Guardian of Genetic Messenger-RNA-Binding Proteins. Biomolecules, 6(1), 18. doi:10.3390/biom6010004
Keywords: Alcohol; Gene Expression; Rna-Binding Proteins; Mrna Splicing; Neurological Diseases; Cancer